2014
DOI: 10.3171/2014.4.spine13925
|View full text |Cite
|
Sign up to set email alerts
|

Posterior lumbar interbody fusion with total facetectomy for low-dysplastic isthmic spondylolisthesis: effects of slip reduction on surgical outcomes

Abstract: Object The management of isthmic spondylolisthesis remains controversial, especially with respect to reduction. There have been no reports regarding appropriate slip reduction. The purpose of this study was to investigate the following issues: 1) surgical outcomes of posterior lumbar interbody fusion (PLIF) with total facetectomy for low-dysplastic isthmic spondylolisthesis, including postoperative complications; 2) effects of slip reduction on surgical outcomes; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…Although many reports have described the surgical outcomes of PLIF [1][2][3][19][20][21][22][23][24][25] , there have been no patient-based satisfaction analyses of PLIF. Patient-based surgical outcomes of PLIF for lumbar spondylolisthesis were previously reported for the first time 15,16) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although many reports have described the surgical outcomes of PLIF [1][2][3][19][20][21][22][23][24][25] , there have been no patient-based satisfaction analyses of PLIF. Patient-based surgical outcomes of PLIF for lumbar spondylolisthesis were previously reported for the first time 15,16) .…”
Section: Discussionmentioning
confidence: 99%
“…Shinya Okuda 1) , Takahito Fujimori 2) , Takenori Oda 3) , Takafumi Maeno 1) , Tomoya Yamashita 1) , Tomiya Matsumoto 1) and Motoki Iwasaki 1)…”
Section: Factors Associated With Patient Satisfaction For Plif: Patieunclassified
See 1 more Smart Citation
“…This criterion has been well accepted by other scholars [14] . Okuda S. et al Reported that deformation of facet joints may lead to accelerated degradation of the spinal stabilization, and to a certain extent, affect the progress of degenerative spondylolisthesis [15] . It has been reported that degenerative lumbar spondylolisthesis could naturally lead to spontaneous stabilization [16] .…”
Section: Evaluation Of the Stability Of Lumbar Spondylolisthesismentioning
confidence: 99%
“…However, there still exists controversies over whether slippage correction may be necessary for spondylolisthesis. Lian et al, reported that PLIF surgery and pedicle screw xation successfully with or without correction resulted in the good postoperative outcome, however, deliberate correction with better imaging results did not necessarily correlate to better clinical outcomes [15] . Karsy M reported that postoperative pain relief and functional recovery were signi cantly better than those obtained via conservative treatment alone [19] .…”
Section: Correction Of Lumbar Spondylolisthesismentioning
confidence: 99%